Effect of nanoparticles on morphology and size of primary silicon and property of selective laser melted Al-high Si content alloys. (September 2021) - Xi, Lixia; Guo, Shuang; Ding, Kai; Prashanth, Konda Gokuldoss; Sarac, Baran; Eckert, Jürgen
Abstract: The coarsening of primary silicon phases is one of the main challenges in the preparation and application of Al-high Si content alloys. In this work, AlSi40 alloys were manufactured by selective laser melting (SLM). The influence of ceramic nanoparticles on the morphology and size of primary Si phase(s) is investigated. With addition of ceramic nanoparticles, large snow-shaped primary Si changes towards a polygonal shape in coarse regions, while blocky primary Si in fine regions shows insignificant change. The size of primary Si in the modified alloy decreases by ~27.1% and ~25.2% in the respective coarse and fine regions compared to that of the unmodified alloy. Due to the refinement and smoothening of primary Si in the modified alloy, the microhardness distribution becomes homogeneous and an average value of ~233 HV0.2 was obtained. The coefficient of friction (COF) value and the wear rate are ~0.44 and ~4.5 × 10 −5 mm 3 N −1 m −1, respectively. An ultimate compressive strength of ~0.76 GPa and a maximum compressive strain of ~7.99% are obtained, increasing by ~21.0% and ~18.0% compared to those of the unmodified alloy. The SLM-fabricated AlSi40 alloys upon heat treatment showed an improved plasticity and slightly decreased strength due to the coarsening of primary Si and grains, decreased solid solution of Si in the matrix as well as accommodation of residual stresses after heat treatment. Highlights: AlSi40 alloys modified with nanoparticles are processed by selective laser melting. The effect of nanoparticles on the morphology and size of primary Si is studied. The properties of AlSi40 alloys with and without nanoparticles are compared. The underlying mechanism for improved properties of composites is revealed.